Limitations of stabilizing effects of fundamentalists: Facing positive feedback traders - Michael Heinrich Baumann; Michaela Baumann; Alexander Erler (Kiel Institute for the World Economy (IfW), 2019)
The authors analyze financial interactions between fundamentalists and chartists within a heterogeneous agent model, focusing on the role of fundamentalists stabilizing prices. In contrast to related studies, which are based on simulations and calculations, they analytically prove that the presence of fundamentalists is not sufficient to avoid asset price bubbles. The behavior of trend followers with bounded leverage can result in exploding prices irrespective of fundamentalists' investment decisions. They derive upper boundaries for positive feedback traders' initial investment necessary to avoid exploding prices. In order to stabilize stock/asset markets, intervention measures might be helpful.
Keywords: D84; G01; G11; 330; heterogeneous agents; feedback trading; fundamentalists; chartists; trend followers; financial bubbles; financial crisis